Synergy of 21st Century Skills (4C) and Mathematical Disposition in the Transformation of Innovative Mathematics Learning Models: A Systematic Literature Review - Ismiyati, Nur (International Journal of Technology and Education Research, 2026)
This study is motivated by the demands of 21st-century education, which emphasize the development of 4C skills (critical thinking, communication, collaboration, and creativity) alongside the importance of mathematical disposition as an affective factor supporting students’ success in mathematics learning. However, studies integrating these two aspects within a unified instructional framework remain limited. Therefore, this study aims to examine research trends, analyze the relationship between mathematical disposition and 4C skills, and identify the most effective innovative learning models in fostering their synergy. This study employed a Systematic Literature Review (SLR) guided by the PRISMA protocol, analyzing 20 articles published within the last decade. Data were collected from reputable academic databases and analyzed using a qualitative descriptive approach through identification, screening, eligibility, and data extraction stages. The findings reveal a significant shift from a partial approach toward the integration of cognitive and affective aspects in mathematics learning. Mathematical disposition shows a positive and significant relationship with 4C skills, although its influence is context-dependent and mediated by factors such as self-efficacy and learning environment. Furthermore, innovative learning models such as Problem-Based Learning, Project-Based Learning, and Realistic Mathematics Education demonstrate more consistent effectiveness in fostering this synergy. This study implies that constructivist and collaborative learning approaches are essential to optimize both students’ 4C skills and mathematical disposition.